Framing Child Abuse: Analyzing Media Coverage of CSA in Lahore's Newspapers (2020-2023) (Journal of Advanced Research in Social Sciences, 2025)
Media coverage significantly influences public understanding and policy responses to child abuse. This study examines the portrayal of child abuse, particularly child sexual abuse (CSA), in Lahore’s newspapers from 2020 to 2023. Findings reveal distinct patterns in coverage frequency, framing, and narrative presentation across English and Urdu newspapers. The analysis highlights issues such as sensationalism, lack of sensitivity, and politicization. Despite these challenges, media coverage remains essential for raising awareness and fostering societal dialogue on child protection. The study emphasizes the need for ethical reporting practices, improved journalist training, and stronger collaboration between media, government, and civil society to effectively address child abuse.